Antihypertensive and cardiovascular effects of catechin-rich oil palm (Elaeis guineensis) leaf extract in nitric oxide–deficient rats - Md. Jaffri, Juliana; Mohamed, Suhaila; Rohimi, Nordanial; Ahmad, Intan Natasya; Mohamed Mustapha, Noordin; Manap, Mohd Yazid (Mary Ann Liebert Inc., 2011)
Oil palm (Elaeis guineensis) leaf extract (OPLE) possesses good ex vivo vasodilation and antioxidant properties. This study evaluated the catechin-rich OPLE antioxidant, antihypertensive, and cardiovascular effects in normal and nitric oxide (NO)–deficient hypertensive rats. OPLE was administered orally (500 mg=kg of body weight=day) to normotensive Wistar rats and Nx-nitro-l-arginine methyl ester (l-NAME)-induced NO-deficient hypertensive rats. OPLE significantly (P < .05) attenuated blood pressure increases, increased serum NO, reduced lipid peroxidation, and showed antioxidant effects in NO-deficient hypertensive rats. OPLE decreased the coronary arteriole wall-to-lumen ratio to near normal values under NO deficiency. Although OPLE showed good antihypertensive and antioxidant effects under NO deficiency, it was not hypotensive to normal rats and produced no chronic cardiovascular toxicity in any of the rats throughout the 12-week study. This is the first report on the in vivo antihypertensive properties of green tea catechins extracted from an alternative source, namely, oil palm leaf, for use as a medicinal food for hypertension and cardiovascular ailments.